2020
DOI: 10.21203/rs.2.19325/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Whole exome sequencing identified mutations causing hearing loss in five consanguineous Pakistani families

Abstract: Background: Hearing loss is the most common sensory defect, and it affects over 6% of the population worldwide. Approximately 50%-60% of hearing loss patients are attributed to genetic causes. Currently, more than 100 genes have been reported to cause non-syndromic hearing loss. It is possible and efficient to screen all potential disease-causing genes for hereditary hearing loss by whole exome sequencing (WES).Methods: We collected 5 consanguineous pedigrees from Pakistan with hearing loss and applied WES in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…DFNB59 is first identified as the causal gene of autosomal recessive deafness, which also plays key role during the signal transmit of auditory nerve 25 . As a hearing‐loss gene, variants of DFNB59 are linked with non‐syndromic hearing loss 141,184–187 . In addition, case reports have reported that PJVK also plays a role in other hearing‐related syndromes like auditory neuropathic spectrum disorder (ANSD) and poor cochlear implants performance 25,188 …”
Section: The Mechanism Of the Pyroptosis Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…DFNB59 is first identified as the causal gene of autosomal recessive deafness, which also plays key role during the signal transmit of auditory nerve 25 . As a hearing‐loss gene, variants of DFNB59 are linked with non‐syndromic hearing loss 141,184–187 . In addition, case reports have reported that PJVK also plays a role in other hearing‐related syndromes like auditory neuropathic spectrum disorder (ANSD) and poor cochlear implants performance 25,188 …”
Section: The Mechanism Of the Pyroptosis Pathwaymentioning
confidence: 99%
“…25 As a hearing-loss gene, variants of DFNB59 are linked with non-syndromic hearing loss. 141,[184][185][186][187] In addition, case reports have reported that PJVK also plays a role in other hearing-related syndromes like auditory neuropathic spectrum disorder (ANSD) and poor cochlear implants performance. 25,188…”
Section: Gsdme/dfna5mentioning
confidence: 99%
“…In summary, GIPC3 mutations have been shown to underlie NSHL associated with DFNB15, DFNB72 and DFNB95. In NSHL, biallelic, nonsense, and shift mutations were also observed in the GIPC3 gene (Chen et al, 1997;Ain et al, 2007;Charizopoulou et al, 2011;Rehman et al, 2011;Diaz-Horta et al, 2012;Sirmaci et al, 2012;Ramzan et al, 2013;Petrova et al, 2021), and more GIPC3 mutation loci are gradually being reported as research progresses (Siddiqi et al, 2014;Ammar-Khodja et al, 2015;Asgharzade et al, 2018;Khan et al, 2019;Bitarafan et al, 2020;Kannan-Sundhari et al, 2020;Zhou et al, 2020; Table 1).…”
Section: Several Common Gipc3 Mutations That Trigger Hereditary Non-s...mentioning
confidence: 99%
“…Whole-exome capture was performed using the BGI-Exome kit V4 and sequenced by BGI-seq500 with 100 bp paired-end sequenc-ing. Sequenced reads were collected and aligned to the human genome reference (UCSCGRCh37/hg19) by the Burrows-Wheeler Aligner (BWA-MEM, version 0.7.10) [10]. In order to validate the mutations identified in the proband and confirm their cosegregation in the pedigree, DNA from all members of the family was performed Sanger sequenced.…”
Section: Mutation Detection and Analysismentioning
confidence: 99%